2006
DOI: 10.1038/sj.emboj.7601367
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus RNA replication is regulated by FKBP8 and Hsp90

Abstract: Hepatitis C virus (HCV) nonstructural protein 5A (NS5A) is a component of viral replicase and is well known to modulate the functions of several host proteins. Here, we show that NS5A specifically interacts with FKBP8, a member of the FK506-binding protein family, but not with other homologous immunophilins. Three sets of tetratricopeptide repeats in FKBP8 are responsible for interactions with NS5A. The siRNA-mediated knockdown of FKBP8 in a human hepatoma cell line harboring an HCV RNA replicon suppressed HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
155
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(163 citation statements)
references
References 53 publications
8
155
0
Order By: Relevance
“…Therefore, another component downstream of PI3K-Akt in the mTOR pathway might be targeted by NS5A. Our previously published results show that the domain I region of NS5A associated with cellular protein FKBP38 (27), which was further confirmed by the claims of another research group that NS5A bound to the 3ϫTPR region of FKBP38 (36). Recent researches have discovered that FKBP38 was a new member of the mTOR pathway and an intrinsic antagonist for mTOR activity (31).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Therefore, another component downstream of PI3K-Akt in the mTOR pathway might be targeted by NS5A. Our previously published results show that the domain I region of NS5A associated with cellular protein FKBP38 (27), which was further confirmed by the claims of another research group that NS5A bound to the 3ϫTPR region of FKBP38 (36). Recent researches have discovered that FKBP38 was a new member of the mTOR pathway and an intrinsic antagonist for mTOR activity (31).…”
Section: Discussionsupporting
confidence: 56%
“…This suggested that FKBP38 played a role in tuberous sclerosis complex-mediated tumor inhibition. Furthermore, FKBP38 has been suggested to be involved in promoting HCV replication via formation of a triple complex with HCV NS5A and Hsp90 (36). These data suggested that FKBP38 might play important roles in HCV infection and pathogenesis.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Some of these proteins, such as hVAP-33 (41), FKBP8 (44), Hsp90 (40,44), and cyclophilin A (39), may participate directly in the replicase complex. Of these proteins, Hsp90 is a chaperone protein and cyclophilin A is a co-chaperone protein.…”
Section: Discussionmentioning
confidence: 99%